Privatization in Africa - Cambell White, Oliver C.; Bhatia, Anita (World Bank, Washington, DC, 2012)
In a way, the story of privatization in Africa reflects some of the problems which have beset many other development processes: lack of political commitment, poor design, insufficient resources, weak management, and corruption. Privatization in Africa is the outcome of a study undertaken during 1995 and 1996. Up to that time, privatization throughout the continent had been slow, with few visible results and a general feeling among observers and donors that African governments' commitment to the process was generally half-hearted. The purpose of the study was to answer three questions about privatization: (i) what has been happening? (ii) What has resulted? And (iii) what could be done to improve the process in terms of outcome. The data and analyses presented to answer these questions fill a significant gap in the published literature on privatization in Africa. The case-study countries were Benin, Burkina Faso, Ghana, Kenya, Madagascar, Nigeria, Togo, Uganda, and Zambia. The study shows that more privatization has been happening across Africa than was generally thought to be the case; but it also raises many issues about how the process has been planned and implemented. The controversy starts with why African governments have privatized. The study maintains that the evidence suggests that most governments have privatized reluctantly and not for the reasons set out in policy statements.